Institutional governance and design principles on collective action for sustainable water management in Vietnam - Ong Quoc Cuong; Vu Duong Quynh; Bui Tan Yen; Sander, Bjoern Ole; Vu Hong Trang; Barnard, Jennifer; Nelson, Katherine (Elsevier, 2025)
Rice production is firmly situated at the nexus between food security, water resources, and greenhouse gas emissions, contributing to climate change. Alternate wetting and drying (AWD) has been suggested as a climate-resilient irrigation practice in Vietnam’s Mekong Delta. This study investigates how irrigation governance affects AWD uptake by applying Elinor Ostrom’s design principles for collective action. Focus group discussions with local agricultural authorities and one-on-one surveys with irrigation service providers were conducted in An Giang Province. The results show that 51 % of the providers reported AWD adoption in the Winter-Spring and Summer-Autumn seasons. Irrigation governance follows a hierarchical structure with nested management levels, and cooperatives and collaborative groups show more substantial institutional capacities than individual providers. However, key governance functions, such as monitoring and sanctioning, remain weakly implemented. Applying Ostrom’s design principles to collective action can improve the adoption of AWD technology. The findings of this study can provide insight into the evolution of irrigation governance and what is needed to implement institutions (rules, regulations, and norms) that would foster collective benefits effectively. The results can be used to analyze other common resource systems or to study the institutional governance of irrigated rice systems in other locations.